Avian roadkills occur regardless of bird evolutionary uniqueness across Europe. (October 2020) - Morelli, Federico; Rodríguez, Ricardo A.; Benedetti, Yanina; Delgado, Juan D.
Highlights: We performed a literature review about bird's roadkill from 9 European countries. We tested the phylogenetic signal of the frequency of roadkill across bird species. Rate of roadkill of birds is not correlated with the evolutionary distinctiveness score. Birds most frequently killed in the roads were Blackbird, House Sparrow, and European Robin. Abstract: Through an extensive literature review and using a large dataset collected from several European studies, we explored the frequency of occurrence of road bird casualties. First, we modelled the inter-specific variation in roadkill' frequency across the avian phylogeny, testing for phylogenetic signal. Then, we explored the association between frequency of roadkill and some avian traits and evolutionary distinctiveness score of species. The rate of roadkill did not show a phylogenetic signal, indicating that the incidence of avian casualties is independent of the phylogenetic position of species. The incidence of roadkill was unrelated to the evolutionary distinctiveness, distribution range size, type of diet, or period of activity of species, but was slightly negatively associated with the species' body mass. This result implies that roadkill is a form of anthropogenic mortality widely generalized concerning avian phylogeny. We highlight that roadkill mitigation measures could benefit from incorporating peculiarities of local or regional avifauna.